THE USE OF MODERN TEACHING METHODS IN THE FIELD OF PHYSICAL EDUCATION AMONG STUDENTS APPLIED IN MIDDLE SCHOOLS FROM THE POINT OF VIEW OF SUPERVISORS IN MAYSAN GOVERNORATE - Lec. Hayder Abdul Hasan Kareem; Lec. Mazin Abdulaaima Kadimm (Proximus Journal Publishing, 2025)
The study aims to identify the most important teaching skills necessary for the student applying in managing the physical education lesson in secondary schools from the point of view of the faculty members in the College of Physical Education and Sports Sciences, University of Misan. The researchers used the descriptive approach using the survey method, in addition to using the teaching skills scale that the researchers modified to be consistent with the reality of the educational environment in Iraq. The study sample was represented by the faculty members, numbering (25), who were selected randomly. The researchers extracted the scientific foundations so that the scale would have scientific standards and be ready to be adopted on the application sample. The researchers reached a set of conclusions, including the selection of (7) teaching skills for the applying student from a total of (22) skills. The teaching skills for the applying student were chosen in a manner consistent with the academic orientation in terms of the specificity of the scientific, practical and theoretical specialization of physical education. The researchers recommended the necessity of working on using modern technology in teaching students all sports activities by displaying video clips, and building cognitive achievement measures for the special laws of sports games, which contribute to registering the student who applies them in the arbitration courses held by sports federations.
Keywords: modern teaching methods; applied students